Analisis Komparasi Cybercrime Web Defacement dan Darknet Exposure di Indonesia (Studi Kasus : Lanskap Keamanan Siber di Indonesia Tahun 2022 dan Tahun 2023) - Saidah, Muthiah As; Saputra, Aggry; Setiawan, Hendi (LPPM Universitas Putera Batam, 2024)
This study aims to analyze the comparison of cyber incidents involving Web Defacement and Darknet Exposure in Indonesia for the years 2022 and 2023, and to evaluate the effectiveness of the mitigation recommendations provided. The method used in this study is the Wilcoxon statistical test to determine significant differences between the incident rates in those two years. The Wilcoxon test results indicate that the Asymp. Sig. (2-tailed) value is 0.008, which, in the case of a one-tailed test, results in a probability of 0.004. This value indicates a significant difference between the Darknet Exposure incident rates in 2022 and 2023. The analysis also suggests that the mitigation recommendations implemented in 2022 were not effective in reducing Darknet Exposure incidents in 2023, as evidenced by an increase in the number of cases. Conversely, for Web Defacement incidents, the Wilcoxon test results show the same Asymp. Sig. (2-tailed) value of 0.008, resulting in a probability of 0.004. This indicates a significant difference between the Web Defacement incident rates in 2022 and 2023. Based on the test results, the mitigation recommendations proved effective in reducing Web Defacement incidents, with a decrease in the number of cases in 2023. From these findings, it can be concluded that cyber incident handling strategies need to be adjusted and strengthened, especially in dealing with Darknet Exposure incidents. Continuous monitoring and evaluation are also crucial for improving the effectiveness of cyber incident management in Indonesia.